Satisfacción del visitante en el complejo turístico Campo Alegre del cantón Montalvo - Isa Sisa, Mayra Johana (2018)
The present development of the investigation was carried out in the city of Montalvo belonging to the Province of Los Ríos in the coastal region of Ecuador, it has several tourist attractions such as the Refuge, Crystal River Complex, Spa Pisagua, Spa the Pearl, Virgin of Los Remedios, among other attractions in which a large number of tourists from different cities attend, are therefore related to the study of visitor satisfaction in the complex due to the limited number of non-specialized staff in the tourism area good attention so that the expectations that visitors require to meet their needs are not met. Therefore we must improve the publicity that the complex has to offer the place and its recreational activities, since it will allow to have more affluence of visitors considering as the main objective the satisfaction of the people that visit the place in such a way that it will help to better the development tourist of that complex.